Clinical Characteristics and Prognostic Factors of Severe COVID-19 - Yang Y; Huang Z; Pei Y; Huang Y; Chen C; Zhou T (Infection and Drug Resistance, 2025)
Yun Yang,* Ziyi Huang,* Yongjian Pei, Yongkang Huang, Chen Chen, Tong Zhou Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Soochow University, Suzhou, Jiangsu, 215004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tong Zhou, Department of Respiratory and Critical Care Medicine, The Second Affiliated Hospital of Soochow University, 1055 San Xiang Road, Suzhou, Jiangsu, 215004, People’s Republic of China, Email zhoutonghxk@163.comPurpose: Coronavirus disease-2019 (COVID-19) has high mortality and has caused heavy economic burden worldwide. In this study, we investigated the clinical characteristic and prognostic factors of patients with severe COVID-19. We aimed to identify the severe cases in early stages to improve the prognosis and mortality.Patients and Methods: We collected the clinical data of 98 patients with severe COVID-19, who were admitted to the Second Affiliated Hospital of Soochow University (Jiangsu, China) from December 2022 to November 2023. The patients were divided into two groups, namely survivors and non-survivors, based on the outcomes of hospitalization. The risk factors affecting the prognosis of severe COVID-19 patients were identified by univariate analysis and multivariate logistic regression analysis. The predictive value of the individual and combined risk factors for the prognosis of severe COVID-19 was evaluated by the area under the receiver operating characteristic curve (AUROC).Results: Compared with survivors, non-survivors had higher white blood cell (WBC) count, neutrophil count, Acute Physiology and Chronic Health Evaluation II (APACHE II) score, and platelet (PLT) count. Moreover, non-survivors exhibited a higher propensity to develop acute kidney injury (AKI) and receive mechanical ventilation (MV) and continuous renal replacement therapy (CRRT). Multivariate logistic regression analysis showed that WBC count, PLT count, APACHE II score, and MV were independent risk factors affecting the prognosis of severe COVID-19 patients, with AUC values of 0.807, 0.690, 0.761, and 0.751, respectively. The AUC of the combined risk factors was 0.897.Conclusion: WBC count, PLT count, APACHE II score, and MV were independent risk factors for the poor prognosis of severe COVID-19 patients. High WBC count, PLT count, and APACHE II score, as well as the use of MV, showed good predictive value for the mortality of severe COVID-19 cases, especially when combined.Keywords: COVID-19, white blood cell, platelet count, APACHE II score, mechanical ventilation